Volleyball Fundamental Movement Learning Model in Primary School - Samsudin Samsudin (OVS LLC, 2021)
The study purpose. This study aims to develop a volleyball fundamental movement learning model with a game-centered approach and test its effectiveness in improving the volleyball learning outcomes of elementary school students